Modified Binary Partition Assisted Broadcast Protocol for Emergency Message Dissemination in VANET - Daiyue Cheng; Guoan Zhang; Xiang Ye (Dianxin kexue, 2015)
A modified binary partition assisted broadcast（MBPAB）protocol was proposed, which was designed for emergency messages dissemination in vehicular Ad Hoc network（VANET）. The protocol divided the communication range into small sectors, and sought the farthest possible nodes in the farthest sector from the sender node to be the forwarding node to increase the dissemination speed by reducing the forwarding hops. A mini distributed inter-frame space（mini-DIFS）in a medium access control（MAC）sublayer was introduced to give the emergency messages a higher access priority to the communication channel compared with other messages. The results demonstrate that MBPAB protocol outperforms benchmarks of the existing broadcast protocols in VANET in terms of communication delay and the average message dissemination speed.